2021
DOI: 10.2139/ssrn.3772087
|View full text |Cite
|
Sign up to set email alerts
|

Home Broadband and Human Capital Formation

Abstract: This paper estimates the effect of home high-speed internet on national test scores of students at age 14. We combine comprehensive information on the telecom network, administrative student records, house prices and local amenities in England in a fuzzy spatial regression discontinuity design across invisible telephone exchange catchment areas. Using this strategy, we find that increasing broadband speed by 1 Mbit/s increases test scores by 1.37 percentile ranks in the years 2005-2008. This effect is sizeable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…For example, Aguirre et al ( 2021 ) found evidence that computers and the internet at home positively impacted English language performance in Columbia. Sanchis-Guarner et al ( 2021 ) found that increasing broadband speed by 1Mbps increases test scores by 1.37 percentiles ranks in the UK. Similarly, Dettling et al ( 2018 ) used data from the U.S. and found that students with broadband access in their postal codes performed better on the SAT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Aguirre et al ( 2021 ) found evidence that computers and the internet at home positively impacted English language performance in Columbia. Sanchis-Guarner et al ( 2021 ) found that increasing broadband speed by 1Mbps increases test scores by 1.37 percentiles ranks in the UK. Similarly, Dettling et al ( 2018 ) used data from the U.S. and found that students with broadband access in their postal codes performed better on the SAT.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the proliferation of the literature on the effect of technology on educational attainment or learning worldwide with mixed results (e.g., Aguirre et al, 2021 ; Sanchis-Guarner et al, 2021 ; Dettling et al, 2018 ; Fairlie et al, 2010 ; Harter & Harter, 2004 ; Cairlie & Robinson 2013 ), there is little empirical work in the context of COVID-19 pandemic. The present study contributes to the sparse literature on the effect of technology access on student learning hours, focusing on the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…From an economic‐perspective, broadband infrastructure is commonly viewed through the lens of a place‐based investment that may boost regional economic growth and provide benefits to both households and firms (Arvin & Pradhan, 2014; Prieger, 2013; Whitacre & Gallardo, 2020). Although job creation/retention and business formation has been a mainstay of broadband‐related research, recent evidence has also linked broadband expansion with firm location decisions (Duvivier, 2019), reducing educational attainment gaps (Hampton et al., 2020), promoting greater human capital formation (Sanchis‐Guarner et al., 2021), advancing gender equality (Bahia et al., 2021), increasing rural housing values (Deller & Whitacre, 2019), and even improving a variety of personal health outcomes (Bauerly et al., 2019).…”
Section: Broadband and Economic Outcomesmentioning
confidence: 99%
“…Through broadband network, learners are no longer subject to various constraints, such as time, distance, and school, and can efficiently acquire the knowledge they need, so that they can accumulate new knowledge more easily (Ardichvili, 2002). Therefore, broadband network can effectively improve learning capabilities and expand access to education (Sanchis‐Guarner et al, 2021). Finally, broadband network provides a faster and less expensive communication method, which promotes extensive exchange of knowledge between R&D personnel and departments and ultimately improves the efficiency of knowledge spillover (Kafouros, 2006).…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%